The Kabbalistic remez and Its Status in Naḥmanides’ Commentary on the Torah - Yisraeli, Oded (The journal of Jewish thought & philosophy, 2016)
Naḥmanides’ commentary on the Torah, in which he combined literal, midrashic, and kabbalistic comments side by side, is one of the best known and most influential exegetical works of the Middle Ages. This article concentrates on the esoteric exegesis in this commentary and argues that Naḥmanides’ kabbalistic interpretation employs two types of exegesis—perush and remez—each of which represents a separate hermeneutic approach and thus a different reading of the biblical text. Focusing on the innovative and less familiar remez approach, the article describes its essence, characteristics, and the historical context of its emergence.